The challenge of the Plus Size fashion consumer in Brazil and the United States: a bibliometric study - Büttner, Ana Julia (2022)
Fashion academic literature did not approach plus-size consumers, nor did the companies. This research aimed to analyze literature in the fashion field concerning overweight people combined with emotional well-being and self-esteem. A quantitative method pointed out countries and journals with relevant academic production. This research suggests a lack of fashion studies and companies that contemplate fashion as a powerful instrument for plus-size consumers. Therefore, they did not contribute to these vulnerable consumers' self-esteem and well-being.